Fermentative metabolic features of doenjang-meju as revealed by genome-centered metatranscriptomics - Dong Min Han; Ju Hye Baek; Dae Gyu Choi; Che Ok Jeon (Food Chemistry: X, 2024)
Fermentative features of doenjang-meju, a traditional Korean soybean brick, were investigated over 45 days via genome-centered metatranscriptomics. The pH value rapidly decreased within 10 days and successively increased after 20 days, along with an initial bacterial growth, including lactic acid bacteria, and subsequent fungal growth, suggesting their association. Polysaccharides and lipids underwent degradation, and amino acids, free sugars, and organic acids increased during the early stage. Metagenome analysis identified Aspergillus, Bacillus, Enterococcus, Staphylococcus, and Leuconostoc as major microbes, which were isolated and genome-sequenced. Metatranscriptomic analysis revealed the major roles of Bacillus and Enterococcus during the early period, shifting to Aspergillus dominance after 10 days. Metabolic pathway reconstruction and transcriptional analysis reveal that Aspergillus primarily decomposed polysaccharides to free sugars; Aspergillus and Bacillus metabolized lipids, free sugars, and organic acids generated by Enterococcus; and Aspergillus and Bacillus were instrumental in amino acid metabolism: their contributions varied by compounds and pathways.